Estudo das propriedades dielétricas da matriz cerâmica FeNbTiO6:(ZnO)x para aplicações em radio-frequência (RF) e microondas - Castro, Armando José Neves de (2014)
In recent years, technological development has been present in all areas of human activity requiring new materials pair meet the demand technologies and new applications generating more and more research. Among the various research areas, the area of ceramic materials has attracted attention from the scientific community , due to the potential applications in devices for microwave and radiofrequency ( RF) . Elect roceramics are rutile type metal oxides whose general structure is repre sented by the structure of MO 2 , MM'O 4 an d MM' 2 O 6 , the site where M can be represented by one or a combination of two or more metal ions ( Ti 4 + , Fe 3 + , NB 5 + etc. ) . This work aims to study the dielectric properties of the matrix FeNbTiO 6 ( FNTO) i n regions of microwave and radio frequency ( RF ) and the effect of addition of Zinc Oxide ( ZnO ) in th e dielectric properties of FNTO . The ceramic FNTO was prepared by solid state reaction with the reactants and activated by grinding calcined at 1075 ° C and then added with ZnO (with concentrations ranging from 0 to 25 % by mass) . All samples were sintered at 1125 ° C. The samples were studied by X - ray diffraction ( XRD ) , the dielectric properties of FNTO sampled and added ZnO were measured by Impedance Spectroscopy and the m ethod of Hakki - Coleman . The X - ray analysis indicates that the FNTO was obtai ned by the proposed synthesis, showing a structure of the ruti le type with tetragonal symmetry. The dielectric property presented in this work showed the dielectric constant ( εr ) and dielectric loss ( Tg δ ) were measured at room temperature in the frequency range from 1Hz - 1 G Hz , the results presented properties to production potential capacitive devices . All samples were investigated in view of possible appli cations in electronic circuits. An alternative to such materials would produce oscillators and dielectric resonator antenna (DRA)